2012
DOI: 10.1016/j.neuroimage.2012.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Functional topography of primary emotion processing in the human cerebellum

Abstract: The cerebellum has an important role in the control and coordination of movement. It is now clear, however, that the cerebellum is also involved in neural processes underlying a wide variety of perceptual and cognitive functions, including the regulation of emotional responses. Contemporary neurobiological models of emotion assert that a small set of discrete emotions are mediated through distinct cortical and subcortical areas. Given the connectional specificity of neural pathways that link the cerebellum wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
178
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 62 publications
(72 reference statements)
21
178
0
10
Order By: Relevance
“…5 Whereas Andela et al found an increase in cerebellar volume in their patients 6 months after cure, our data show a lower cerebellar volume, supporting the results published by Santos et al in 2014, 31 who also found a significant reduction of cerebellar volume in patients with active CS. These findings correspond to the presence of glucocorticoid receptors in the cerebellum, 16 and could explain our results of lower cerebellar volume, which are confirmed by the results of Santos et al and Momose et al Interestingly, we did not find a significant correlation between the duration of illness and reduction of GM, or between the elevation of cortisol, ACTH, and DHEA-S and reduction of GM, which is most likely to be due to the relatively small sample size of only 19 patients.…”
Section: Discussionsupporting
confidence: 90%
“…5 Whereas Andela et al found an increase in cerebellar volume in their patients 6 months after cure, our data show a lower cerebellar volume, supporting the results published by Santos et al in 2014, 31 who also found a significant reduction of cerebellar volume in patients with active CS. These findings correspond to the presence of glucocorticoid receptors in the cerebellum, 16 and could explain our results of lower cerebellar volume, which are confirmed by the results of Santos et al and Momose et al Interestingly, we did not find a significant correlation between the duration of illness and reduction of GM, or between the elevation of cortisol, ACTH, and DHEA-S and reduction of GM, which is most likely to be due to the relatively small sample size of only 19 patients.…”
Section: Discussionsupporting
confidence: 90%
“…It would also be interesting to compare affective stimuli that vary in their modality of presentation (e.g., visual vs. auditory; Royet et al, 2000). In this context, however, it should be noted that there is considerable interindividual variability in affective and neural responses to specific emotional categories (Baumann & Mattingley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The IAPS provides a standardized approach to evoking and assessing emotions in a controlled manner and has been extensively tested for reliability and validity (Bradley & Lang, 2007). The 120 images (neutral = 48, positive = 36, negative = 36) were selected based on the IAPS normative ratings, in line with several earlier neuroimaging studies (e.g., Baucom, Wedell, Wang, Blitzer, & Shinkareva, 2012;Baumann & Mattingley, 2012;Crawford & Cacioppo, 2002;Keil et al, 2002). The neutral images were chosen to be low in arousal (mean = 2.66; SD = 0.38) and intermediate in valence (mean = 4.91, SD = 0.05), whereas positive and negative images were chosen to be equally high in arousal (positive: mean = 5.98, SD = 0.85; negative: mean = 6.28, SD = 0.73) and opposite in valence (positive: mean = 7.20, SD = 0.66; negative: mean = 2.18, SD = 0.45).…”
Section: Learning Phasementioning
confidence: 99%
“…The anatomical studies also provide supportive evidence on the connections between cerebellum and other cortical and subcortical areas associated with emotional processing including limbic system and prefrontal cortex. The emotional changes observed in patients with cerebellar syndrome and the activation of cerebellum following the emotional stimuli also support this prospect (37)(38)(39). Furthermore, the anatomoclinical analyses of cerebellum have indicated that the posterior vermis, or limbic cerebellum, is mainly involved in the regulation of emotion and affect (40).…”
Section: The Role Of Cerebellum In Emotionmentioning
confidence: 75%
“…Many studies have investigated the relationship between cerebellum and emotions. In an study using functional MRI , Baumann and Mattingly found that all five primary emotions evoked activity in the cerebellum, including vermis and the intermediate parts of the cerebellar hemispheres (38). The reduced ability to experience pleasant feelings, but normal unpleasant emotions experience was found in patients with cerebellar lesions (41).…”
Section: The Role Of Cerebellum In Emotionmentioning
confidence: 99%